2008
DOI: 10.1155/2008/478325
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Adenocarcinoma Arising from Abdominal Wall Endometriosis

Abstract: Endometriosis is a frequent benign disorder. Malignancy arising in extraovarian endometriosis is a rare event. A 49-year-old woman is presented with a large painful abdominal wall mass. She underwent a myomectomy, 20 years before, for uterus leiomyoma. Computed tomography suggested that this was a desmoid tumor and she underwent surgery. Histological examination showed a clear cell adenocarcinoma associated with endometriosis foci. Pelvic ultrasound, computed tomography, and endometrial curettage did not show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…Twenty‐seven cases of malignancy arising in a focus of scar endometriosis (mostly in abdominal wall), including the present case, have been reported in the literature between January 1966 and November 2011 and are summarized in Table . Of these 28 total cases, 18 showed clear cell carcinoma, 4 showed endometrioid carcinoma, 2 had papillary serous carcinoma, 1 reported carcinosarcoma and 1 reported adenocarcinoma.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Twenty‐seven cases of malignancy arising in a focus of scar endometriosis (mostly in abdominal wall), including the present case, have been reported in the literature between January 1966 and November 2011 and are summarized in Table . Of these 28 total cases, 18 showed clear cell carcinoma, 4 showed endometrioid carcinoma, 2 had papillary serous carcinoma, 1 reported carcinosarcoma and 1 reported adenocarcinoma.…”
Section: Discussionmentioning
confidence: 92%
“…In these studies, the average reported age at diagnosis was 47 years old. The great majority of cases arose at a long interval from cesarean section scars, with some exceptions: one case followed myomectomy, one case followed hysterotomy, one case followed laparotomy for uterine perforation, five cases followed episiotomy, and one followed open sterilization . Most of these procedures would allow endometrium to implant at the surgical incision site.…”
Section: Discussionmentioning
confidence: 99%
“…More extensive surgery was reported in 6 cases, including resection of mons pubis, [ 31 ] cystectomy, [ 29 , 36 , 44 ] and colectomy. [ 33 , 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of cases, a total hysterectomy was performed with bilateral salpingooophorectomy, 8,9,17,19,32 omentectomy, 12,25,29 and pelvic lymphadenectomy. 21,22,28 When hysterectomy was not performed, curettage to exclude primary endometrial carcinoma was performed. 14,17,23,26,32 Chemotherapy was administered to 74% of the patients.…”
Section: Resultsmentioning
confidence: 99%